On the Problem of the Semantic Structure of Consciousness - Kravtsov, G.G.; Kravtsov, O.G. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2022)
In the article, the authors consider the methodological origins and foundations of psychological science. They point out the impossibility of a mechanical transfer of the paradigm and explanatory principles of natural science to the field of psychology, in which such an approach inevitably leads to a methodological dead end. A person becomes part of a deterministic relationship, losing their most important trait — their freedom. Lev Vygotsky proposed an approach that offers a path beyond this outdated methodology. In the cultural-historical approach, the central concept of psychology is the category of personality, while consciousness serves as the subject of study. However, Vygotsky interpretats consciousness in a significantly different way than it had been in psychology before him. He writes about the systemic and semantic structure of consciousness and it is this aspect that is primary for Vygotsky. The authors consider the works of Lev Vygotsky’s closest disciples and associates in this context. In these works, the problem of consciousness and the relationship between sense and meaning is solved in a manner different from traditional psychology. A meaning is always a generalization. Consciousness operates these generalizations. In this article, the authors discuss the problems of theoretical and empirical generalization in the works of Vasily Davydov. The authors conclude that the solution to the problem of generalization, as proposed by Davydov, leads away from the scientific tradition initiated by the works of Lev Vygotsky and his followers. В статье авторы рассматривают методологические истоки и основания психологической науки. Авторы указывают на невозможность механического перенесения естественнонаучной парадигмы и объяснительных принципов на психологическое содержание. Такой подход в психологии с неизбежностью приводит в методологический тупик. Человек оказывается частью детерминистических отношений и теряет самое главное — свою свободу. Выход за пределы этой старой методологии в своем подходе предложил Л.С. Выготский. В культурно-историческом подходе центральным понятием психологии является категория личности, а предметом изучения становится сознание. Но трактовку сознания Л.С. Выготский понимает существенно иначе, чем это имело место до него в психологии. Он пишет о системном и смысловом строении сознания. Причем для Л.С. Выготского первичен именно смысл. В этом контексте авторы рассматривают работы ближайших учеников и соратников Л.С. Выготского. В этих работах проблема сознания и соотношение смысла и значения решается иначе, чем в традиционной психологии. Значение — это всегда обобщение. Именно этими обобщениями и оперирует сознание. В статье авторы обсуждают проблемы теоретического и эмпирического обобщения в работах В.В. Давыдова. Авторы приходят к выводу о том, что решение проблемы обобщений, предложенное В.В. Давыдовым, уводит нас от научной традиции идущей от трудов Л.С. Выготского и его последователей.